KEBIJAKAN HUKUM PIDANA DALAM PERAMPASAN ASET PERKARA TINDAK PIDANA KORUPSI UNTUK MEMAKSIMALKAN PEMULIHAN KEUANGAN NEGARA - Beny Kristanto (2023)
Corruption in Indonesia continues to show an increase from year to year, both in terms of the number of cases that occur and the amount of state financial losses, the acts of corruption committed are also increasingly systematic with a scope that enters all aspects of people's lives. The decline in the Indonesian Corruption Perceptions Index shows that the eradication of corruption in Indonesia has not been running optimally. In addition to the handling of criminal acts of corruption that have not been optimal, recovery of state losses has also not been optimal. This study uses an normative juridical approach. This paper wants to see how criminal law policies in asset recovery at every stage of handling corruption can maximize state financial recovery at this time and how the criminal law policy in asset recovery at every stage of handling corruption can maximize state financial recovery in the future. Recovery of assets in eradicating criminal acts of corruption currently still places asset confiscation as an additional crime so that asset confiscation is still based on the defendant's guilt (conviction based asset forfeiture) and the process of confiscating assets follows the process of upholding criminal acts of corruption so as to maximize the recovery of state finances, the active role of law enforcement officials is required at every stage of handling criminal acts of corruption, in the future, in addition to confiscating assets based on the guilt of the accused (conviction based asset forfeiture), it is necessary to confiscate assets without conviction (non conviction based asset forfeiture) for overcoming obstacles to the implementation of asset confiscation of convicted corruption convicts based on mistakes such as when the perpetrators of corruption run away so as to maximize efforts to recover state losses due to corruption